The processing of homographic morphemes in Chinese: an ERP study. Issue 1 (2nd January 2017) - Wu, Yan; Tsang, Yiu-Kei; Wong, Andus Wing-Kuen; Chen, Hsuan-Chih
ABSTRACT: The processing of homographic morphemes during Chinese word recognition was investigated by recording event-related potentials (ERPs) in a masked priming lexical decision experiment. There were four conditions. In the morpheme condition, the homographic morphemes in primes and targets had the same interpretations (e.g. "公園-public garden/park" and "公眾-public people/the public"). In the homograph condition, they had different interpretations (e.g. "公雞-male chicken/cock"). Semantic-sharing (e.g. "草地-lawn") and unrelated (e.g. "嗅覺-olfaction") conditions were also included. Compared to the unrelated condition, the morpheme and homograph primes produced a comparable P200. In contrast, N400 priming was identified only in the morpheme condition. Semantic sharing produced relatively weaker effects. These findings indicate that homographic morphemes are activated during word recognition even though in principle, whole-word processing is more efficient. The results are discussed with reference to morpho-orthographic and morpho-semantic processing.